"Wild barley serves as a source for biofortification of barley grains". (June 2019) - Wiegmann, Mathias; Thomas, William T.B.; Bull, Hazel J.; Flavell, Andrew J.; Zeyner, Annette; Peiter, Edgar; Pillen, Klaus; Maurer, Andreas
Highlights: Wild barley offers a broad variation for grain nutrient concentrations. Most grain nutrient concentrations are negatively correlated with grain yield. Identification of genomic regions associated with nutrient concentrations. Abstract: The continuing growth of the human population creates an inevitable necessity for higher crop yields, which are mandatory for the supply with adequate amounts of food. However, increasing grain yield may lead to a reduction of grain quality, such as a decline in protein and mineral nutrient concentrations causing the so-called hidden hunger. To assess the interdependence between quantity and quality and to evaluate the biofortification potential of wild barley, we conducted field studies, examining the interplay between plant development, yield, and nutrient concentrations, using HEB-YIELD, a subset of the wild barley nested association mapping population HEB-25. A huge variation of nutrient concentration in grains was obtained, since we identified lines with a more than 50% higher grain protein, iron, and zinc concentration in comparison to the recurrent parent 'Barke'. We observed a negative relationship between grain yield and nutritional value in barley, indicated by predominantly negative correlations between yield and nutrient concentrations. Analyzing the genetic control of nutrient concentration in mature grains indicated that numerous genomic regions determine the final nutritional value of grains and wild alleles were frequently associated with higher nutrient concentrations. The targeted introgression of wild barley alleles may enable biofortification in future barley breeding.